Hepatitis B in Organ Transplantation—Current Evidence and Clinical Gaps - Oscar A. Fernandez‐Garcia; Britta L. Hirsch; Irene A. Abela; Karen E. Doucette (Transplant Infectious Disease, 2026)
ABSTRACT Over the past several decades there have been significant advances in nucleos(t)ide analogue (NA) antiviral therapy for hepatitis B virus (HBV) and global expansion of primary prevention through immunization. Despite this, HBV remains a leading cause of chronic liver disease globally, affecting over 250 million people. NA therapy has dramatically reduced the need for liver transplantation in HBV and transformed post‐transplant outcomes from historically poor to excellent. Similarly, the outcomes of kidney transplant recipients with HBV under NA therapy are now similar to those without HBV. Kidney and other non‐liver recipients, previously exposed to hepatitis B as demonstrated by a positive antibody to hepatitis B core antibody (anti‐HBc) while at risk for reactivation posttransplant have excellent outcomes when prevention strategies of either HBV monitoring or NA prophylaxis are utilized. The advances in HBV antiviral therapy have also led to increasing evidence that the organ donor pool can be expanded not only through the use of donors with positive anti‐HBc, but also those who are hepatitis B surface antigen (HBsAg) positive. In this review, we summarize the current state of the evidence regarding HBV amongst organ donors and recipients of liver and non‐liver organ transplants as well as the persisting gaps in evidence and opportunities for further research.